Potential Use of some Petal Extracts against Xanthomonas campestris pv. campestris - Bhardwaj, S.K.; Singla, S.K.; Bhardwaj, R.K. (Our Nature, 2012)
The aqueous petal-extracts of 20 plants were screened by agar diffusion methods for their antibacterial activity against Xanthomonas campestris pv. campestris, a causal organism of black rot of cabbage and cauliflower. X. campestris pv. campestris was found most sensitive to the petal extracts of Tagetes erecta and Chrysanthemum coronarium. Some of the other plants such as Acacia fernesiana, Anthocephalus cadamba, Bombax malabaricum, Lathyrus odoratus, Rosa damascena and Thevetia nerifolia also showed the inhibitory effect against the test bacteria. DOI: http://dx.doi.org/10.3126/on.v9i1.5739